The impact of training exercises Albulayomterc in the development of forms of muscular strength of lower limbs to accomplish the long jump - abdlameer , zaina (Journal of Physical Education, 2010)
This study contains five chapters the first one consists of introduction and importance which deals with effect of using pliometeric exercises in growing muscular strength on low limbs and complete achiement with less energy and time . It is experimental program that consist of (40) women students from Diyla university – college of sport education . The researcher used in this study tests of muscular strength for each of explosion power and statistic method (spss) . The researcher get to ;1.The using of Pliometeric exercises regularly os active of increase explsion power for muscles of limbs .2.The growth of explosion power for muscle of limbs , back and arms with using Pliometeric exercises effect positive in improve the level of achievement in long Jump for student .3.The growth of speed power for muscles of stomach , back and arms by using Pliometeric effect positive to improve the level of achievement in long Jump for students .